Development of Advance Care Planning-Based Discharge Planning to Enhance the Continuity of Palliative Care - Viesca Septianata; Tuti Afriani; Hening Pujasari; Andi Amalia Wildani; Hana Mutiasari (Indonesian Journal of Global Health Research, 2026)
The demand for palliative care in Indonesia continues to rise as more patients live with chronic and life-limiting conditions. Yet, discharge planning—which should serve as a bridge between hospital care and home care remains limited, particularly when it is not integrated with Advance Care Planning (ACP). This study aimed to design an ACP-based discharge planning model that supports smoother transitions and strengthens continuity of care for palliative patients after hospital discharge.  A descriptive design with a developmental action research approach was carried out at the Hospital. Thirty nurses participated through surveys, complemented by in-depth interviews with the head nurse, nursing committee, and nursing division, as well as direct observation of clinical practice. This study used a purposive sampling technique, with data collected through observations, in-depth interviews, and structured surveys, and analyzed using thematic analysis for qualitative data and descriptive analysis for quantitative data to explore nurses’ knowledge, attitudes, and readiness in implementing ACP-based discharge planning. Data were analyzed descriptively and further explored using SWOT analysis and a fishbone diagram to map strengths, weaknesses, opportunities, threats, and root causes. Findings showed that most nurses understood the concept of ACP (80%) and expressed readiness to be involved, although the majority (73.3%) had never received formal training. Key barriers included limited empathic communication skills, the absence of standard operating procedures (SOPs), and the lack of standardized ACP forms. As an initial step, the study produced draft SOPs, technical guidelines, and ACP forms, which were considered useful but still require refinement and pilot testing. Overall, ACP-based discharge planning has strong potential to improve continuity of care and enhance the quality of life for palliative patients at home. Its success, however, will depend heavily on sustained managerial support, continuous training for nurses, and the active involvement of patients and their families in the care process.